Death beyond Disavowal : The Impossible Politics of Difference - Hong, Grace Kyungwon (Book collections on Project MUSE., 2015)
'Death Beyond Disavowal' utilises 'difference' as theorised by women of colour feminists to analyse works of cultural production by people of colour as expressing a powerful antidote to the erasures of contemporary neoliberalism.